Enhanced anti-tumor efficacy of tumor-infiltrating lymphocytes by GITR agonist in ovarian cancer - Jung, Daun; Goh, Ah-Ra; Kim, Ki Yeon; Lee, Ji Min; Lee, Eun Ji; Hwang, Sohyun; Kang, Haeyoun; Park, Hyun; An, Hee Jung (Frontiers in Immunology, 2025)
BackgroundAdoptive cell therapy (ACT) using autologous tumor-infiltrating lymphocytes (TILs) is a personalized immunotherapy that has shown promising clinical results in various tumor types. Although TILs are associated with improved survival in patients with ovarian cancer (OC), their therapeutic efficacy remains limited. Therefore, novel strategies to enhance the anti-tumor activity of TILs are needed to improve outcomes in OC treatment.MethodsSingle cells were isolated from tumor tissues of patients with high-grade serous carcinoma (HGSC) and expanded for 14 days in the presence of IL-2 under four different conditions: (1) control (W), (2) PD-1 antagonist (WI), (3) PD-1 antagonist + IL-15 + IL-21 (WIO), and (4) PD-1 antagonist + IL-15 + IL-21 + GITR-agonist (WIOG). Following validation of TIL purity and activation phenotypes by flow cytometry, RNA sequencing was performed to elucidate the underlying mechanisms. In vitro efficacy was assessed using a 7-AAD/Far-Red cytotoxicity assay against autologous tumor cells, and in vivo efficacy was evaluated in NSG mice bearing subcutaneous patient-derived tumor cell xenografts (PDCX).ResultsOn day 14, the WIOG group showed a 1.3-fold increase in expansion compared to the control group, along with a high CD8+/Treg ratio (454.6). Furthermore, both CD8+ and CD4+ T cells in the WIOG group exhibited elevated Granzyme B expression. RNA sequencing identified 279 upregulated genes associated with T cell activation (CSF2, TNFRSF4), cytotoxicity (IFNG, GZMB), and anti-apoptosis (BMF, BCL2L1). Compared to the controls, the WIOG group demonstrated a 1.9-fold increase in cytolytic activity in vitro and a 56% reduction in tumor growth in the patient-derived tumor cell xenograft (PDCX) model.ConclusionsTaken together, we demonstrated that the addition of an agonistic GITR antibody during the early phase of TIL culture increased the CD8+ T cell to Treg cell ratio and enhanced anti-tumor T cell immunity. Enhancing TILs with a GITR agonist may be beneficial for improving the clinical outcomes of TIL-based ACT in OC.